Censorship: Most Important Debate of the Decade in the Brazilian Political Scenario - Guimarães de Medeiros, José Edil (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
In his book Contra Toda Censura (Against All Censorship, in a literal translation, no official English translation available), the diplomat Gustavo Maulstach warns us that we are living in times of reversal of this trend with "an increasing number of people abandoning the fundamental principle of freedom of expression in favor of a belief in tutored public debate." With astonishment, I predict the debate on freedom of expression to be the most important of this decade in Brazilian politics. Unfortunately, the classical liberal position of protecting liberty against tyranny does not seem to be the most widely agreed upon at the moment. Concerned about this situation, Maultasch seeks to defend complete freedom of expression on solid grounds, re-examining established arguments and exposing new ones. For this reason, Contra Toda a Censura is a necessary book for the Brazilian public debate, which arrives at a good time.